Análisis jurídico al juicio de inventario según el Código Orgánico General de Procesos - Bayas Tenesaca, María Magdalena (2020)
One of the rights enshrined in the Constitution of the Republic of Ecuador is legal certainty, which refers to the existence of previous, clear and public legal norms, as indicated by the General Organic Code of Processes when dealing with the judgment of inventory not it provides for the possibility of carrying out a new appraisal of the inventoried assets when a period of more than two years has elapsed without the partition having been made, a situation that the repealed Civil Procedure Code did allow, under this background, the present investigation entitled legal analysis The inventory judgment according to the General Organic Code of Processes, sought to describe how the indicated legal vacuum affects the interests of the procedural subjects. The described problem was studied applying the inductive and analytical methods; for the objectives that were reached, it was a field investigation, which has a qualitative approach, with a non-experimental design; the population that was studied were the Judges of the Unidad Judicial de Familia, Mujer, Niñez y Adolescencia of Riobamba city and legal professionals who have sponsored inventory trials under the rules of the General Organic Code of Processes, who were he applied a questionnaire to them; the result of the investigation indicated that there are divided criteria among the judges, since some magistrates do accept the request to carry out a new appraisal of the inventoried assets when a period of more than two years has elapsed without the partition having been made, which that generates legal uncertainty among citizens